1990
DOI: 10.1182/blood.v76.11.2303.2303
|View full text |Cite
|
Sign up to set email alerts
|

Induction of interleukin-6 during human immunodeficiency virus infection

Abstract: Interleukin-6 (IL-6), a multifunctional cytokine produced in monocytes, fibroblasts, and other cell types, is induced by a variety of stimuli, including bacteria, viruses, and other cytokines. When normal monocyte cultures were exposed to a monocytotropic strain of human immunodeficiency virus (HIV), HTLV-IIIBa-L, significant levels of IL-6 bioactivity were detected in the culture supernatants after 12 to 43 days of incubation, at a time when there was associated evidence of HIV production. Similarly, when nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0
2

Year Published

1993
1993
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(45 citation statements)
references
References 48 publications
2
41
0
2
Order By: Relevance
“…As in previous studies [26][27][28] we found elevaied mean plastna IL-6 levels in HI V-infeeled patients. However, most of our HI Vinfeeted palients (7S% of Group 2 and 47".. of Group 3 palienis) had no delectable 1 L-6 levels.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As in previous studies [26][27][28] we found elevaied mean plastna IL-6 levels in HI V-infeeled patients. However, most of our HI Vinfeeted palients (7S% of Group 2 and 47".. of Group 3 palienis) had no delectable 1 L-6 levels.…”
Section: Discussionsupporting
confidence: 89%
“…HIV-infected patients elevated serum or plasma 1 L-6 levels were described in several studies [26 28]. Birx et al [28] described serum IL-6 levels to be correlated with serum [gG levels. Amadori et iil.…”
Section: Introductionmentioning
confidence: 99%
“…Atrophy of the T cell-dependent areas in the lymph nodes of MCD has already been reported [26], and data from our group show that the immunological disturbances in MCD were similar to those seen in HIV infection in Table 1 and [5]. Thus T cell dysfunction, NK cell dysfunction, polyclonal B cell activation, and dysregulation of IL-6 secretion by monocytes are features of both MCD and HIV infection [27][28][29][30]. In MCD patients, cell dysfunction also results in apoptosis [9], a shared feature of HIV infection [24,[31][32][33].…”
Section: Discussionsupporting
confidence: 69%
“…For determination of IL-6 activity in plasma, B9 cells were used in a standard assay as described [11]. Briefly, serial dilutions of heat-inactivated plasma samples and recombinant Escherichia coli-derived IL-6 (Amersham, Aylesbury, UK) were distributed to 96-well flat-bottomed plates (Nunc).…”
Section: Cell Culture Supernatant Preparationmentioning
confidence: 99%